Association Between Metformin Use and the Risk, Prognosis of Gynecologic Cancer - Yao, Kui; Zheng, Heng; Li, Tao (Frontiers in Oncology, 2022)
Background: For gynecological cancer patients, the beneficial effect of metformin use remains controversial due to inconsistent results of published articles. By conducting a meta-analysis, we aimed to evaluate the effect of metformin in reducing the risk and improving the survival of gynecological cancer among women with diabetes mellitus (DM). Methods: Article exploring association between metformin use and the risk, prognosis of gynecologic cancer in DM were searched in the databases: PubMed, Web of Science, SCOPUS, EMBASE, EBSCO and PROQUEST. Articles were published before May 2022. All the studies were conducted using STATA 12.0 software. Results: The meta-analysis showed no significant association between metformin use and risk of gynecologic cancer in DM with a random effects model (odds ratio (OR)/relative risk (RR) = 0.91, 95% confidence intervals (CI) 0.77 to 1.08, I2 = 84.2%, p < 0.001). Metformin use was associated with reduced overall survival (OS), progression-free survival (PFS) of gynecologic cancer in DM with random effects models (OS: hazard ratio (HR) = 0.60, 95% CI 0.49 to 0.74, I2 = 55.2%, p = 0.002; PFS: HR = 0.55, 95% CI 0.33 to 0.91, I2 = 69.1%, p = 0.006), whereas no significant association were showed between metformin use and recurrence free survival (RFS), cancer-specific survival (CSS) of gynecologic cancer in DM with random effects models (RFS: HR = 0.60, 95% CI 0.30 to 1.18, I2 = 73.7%, p = 0.010; CSS: HR = 0.78, 95% CI 0.43 to 1.41, I2 = 72.4%, p = 0.013). Conclusions: In conclusion, this meta-analysis indicated that metformin may be a useful adjuvant agent for gynecological cancer with DM, especially for patients of ovarian cancer and endometrial cancer patients.